Management of false passage complication during operative hysteroscopy - T. Hota; O. M. Abuzeid; R. Raju; J. Holmes; J. Hebert; M. I. Abuzeid (Middle East Fertility Society Journal, 2022)
Abstract Background False passage is a possible complication during operative hysteroscopy and can lead to termination of the intended procedure. The aim of this study is to describe two techniques to overcome the complication of false passage during operative hysteroscopy. Results This is a retrospective case series of 9 patients who had a false passage during operative hysteroscopy for Müllerian anomaly or endometrial polyps. The diagnosis was immediately made by visualization of a lattice network of myometrial fibers without normal landmarks of the endometrial cavity and tubal ostia. Once a false passage was suspected, an attempt was made to overcome this complication and complete the intended operative hysteroscopy. The hysteroscope was slowly withdrawn to identify both the false passage and the opening towards the internal cervical os. The hysteroscope was tilted towards the opening to the internal cervical os, and it was carefully advanced under direct vision into the endometrial cavity. In two patients, this technique failed because the opening to the internal cervical os was small, so the bridge of tissue between the internal os and false passage was partially divided using hysteroscopic scissors or a straight resectoscope loop, allowing for entry into the endometrial cavity. The intended procedures were completed successfully in all patients. No intraoperative or postoperative complications occurred as a result of the two techniques. Conclusions The techniques described in this study, to overcome false passage during operative hysteroscopy, appear to be safe, effective, and easy to perform. They enable the surgeon to complete the intended procedure.